Water policy in the Philippines issues, initiatives, and prospects - Rola, Agnes C.; Pulhin, Juan M.; Hall, Rosalie Arcala (Global issues in water policy, 2018)
This book describes challenges in the policy and practices of the various water sectors in the Philippines that have led to water conflicts. Such conflicts arise in the nature of rural-urban competition, trans-administrative boundary issues, and inconsistencies between customary and state rules, and even within state rules. Using inter-, multi- and trans-disciplinary approaches, and analysing from various scales - community, local and national governments. The book discusses policies and strategies needed towards achieving water security especially for the poor. Reflective of the complex and urgent water policy and governance issues in many developing countries, the book offers valuable lessons and insights to policy makers, water sector managers, planners and regulators as well as to academics, researchers and students.